1992
DOI: 10.1128/aac.36.6.1236
|View full text |Cite
|
Sign up to set email alerts
|

Clindamycin, erythromycin, and roxithromycin inhibit the proinflammatory interactions of Pseudomonas aeruginosa pigments with human neutrophils in vitro

Abstract: The Pseudomonas aeruginosa-derived phenazine pigments pyocyanin and 1-hydroxyphenazine (1-hp) prime human neutrophils for enhanced, stimulus-activated release of superoxide and myeloperoxidase (MPO), respectively. In the present study, the modulatory potentials of the antimicrobial agents clindamycin, eythromycin, and roxithromycin (10 and 20 ,ug/ml) on the prooxidative interactions of pyocyanin and 1-hp (12.5 FM) with human neutrophils have been investigated. Clindamycin, erythromycin, and especially roxithro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A considerable amount of evidences have also accumulated showing that several macrolides are capable of influencing the function of phagocytic cells [22][23][24][25][26]. In most of those experiments, the concentrations of macrolides affecting the PMN function were much higher than the respective achievable serum concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable amount of evidences have also accumulated showing that several macrolides are capable of influencing the function of phagocytic cells [22][23][24][25][26]. In most of those experiments, the concentrations of macrolides affecting the PMN function were much higher than the respective achievable serum concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…40,46 Preventing neutrophil migration and suppressing neutrophil chemotactic activity at inflammatory sites of the lungs is thought to contribute to the clinical effectiveness of macrolides in the treatment of chronic inflammatory airway disease. 39,58,59 One theory as to why the drugs are effective in reducing neutrophil activity is the high intracellular concentrations they achieve. Macrolides are neutral compounds in the blood and readily cross cell membranes.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…62 Possible antioxidant action was theorized to be partly responsible for the clinical effectiveness of macrolide antibiotics in inflammatory diseases. 46,56,58 Treatment with erythromycin significantly decreased intracellular oxidative capacity in neutrophils. 46 Substantial inhibition of superoxide generation by human neutrophils in vitro was seen after treatment with erythromycin and roxithromycin.…”
Section: Oxidant Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has recently been reported that subminimal inhibitory concentrations of CLDM may influence bacterial viability, toxin production, and host response. For example, CLDM promotes phagocytosis of bacteria by neutrophils (29,30), suppresses the production of hemolysin by E. coli (1), inhibits the proinflammatory interactions of Pseudomonas aeruginosa-derived pigments by neutrophils (21), and reduces the amount of exotoxin released by Clostridium perfringens (26). On the other hand, ceftazidime (CAZ) is an effective antibiotic against E. coli, but when E. coli is killed by CAZ, large quantities of endotoxin are released (3,4,10,25).…”
mentioning
confidence: 99%